The Role of Managerial Leadership in Sustainable Business Development - Aden Tatag Surya Bhara Dhaksa; Mahfudz Mahfudz (Yayasan Riset dan Pengembangan Intelektual, 2024)
Managerial leadership is an effort to achieve goals by accommodating people through good communication. The conflict in this research emerged in the context of a chicken farming company in Central Java, involving various aspects that require careful understanding and handling. This research aims to explore the implementation of managerial leadership in developing sustainable business in livestock companies in Central Java. This research method uses a qualitative research type. In this research, the approach used is a case study. This research was carried out by the researchers themselves among owners and managers of livestock companies in Central Java. The results show that company management is highly involved in developing sustainable innovation, creating a creative environment, and ensuring top-level commitment. Corporate leaders face challenges such as lack of resources, internal resistance, and policy coordination, which they overcome through strategic approaches, including improved communications, resource management, and policy adjustments. The solutions taken include resource diversification, internal coordination, balance management of profitability and sustainability, external partnerships, technology implementation, and continuous evaluation.